Obama's energy policy: the energy plan is in reality a climate change plan - Matzke, R (Oxford Institute for Energy Studies, 2009)
The US administration’s energy plan has attracted global attention not because it meets the energy needs of US industry and US consumers but rather, because it is a plan that will result in the reduction of climate changing CO2 industrial emissions in the use of fuel to create energy. The plan is bold, aggressive, challenging, controversial, expensive, and long overdue. Its legislative version is greater than 1000 pages and should be referred to in its original form for those seeking a better understanding than can be presented in this brief article.